The effect of liquid smoke treatment on physical stability and impact toughness chicken feather fibre (CFF) as reinforcement in composites - Muslimin, Mukhlis; Saleh; Seng, Ahmad; Wirawan, Willy Artha; Harbelubun, Mohammad Muzni; Rais, Sandi; Isham, Muhammad Alfajri (Penerbit Universiti Kebangsaan Malaysia, 2023)
The objective of this study was to determine the effect of liquid smoke treatment on chicken feather fibres (CFF) on the morphology and impact toughness of composites reinforced with CFF. The experiment was carried out by measuring the density of CFF, followed by immersion in liquid smoke for 1, 2, and 3 hours. All of the fibers, including one without the immersion treatment, were then inserted into the oven at a temperature of 40 °C for 30 min. The morphological assessments were done using a scanning electron microscope (SEM) and the impact test according to the ASTM D5942-96 standard on the Charpy method impact tester. The SEM results showed that the fibers without immersion had a multitude of impurities at the surface, while with immersion treatment, the fibers had a more clean and rough surface. Impact test results showed that the fiber-reinforced composite without treatment was 61,583 Kj/m2, while the fiber-reinforced composite with immersion treatment for 1, 2, and 3 hours increased by 63,894 Kj/m2, 71,061 Kj/m2, and 80,538 Kj/m2. Treatment for 3 hours significantly increased the strength of the composite by 30.78%.